Pemanfaatan Panel Surya Fotovoltaik untuk Energi Berkelanjutan di Daerah Terpencil - Sari, Dewi Puspita; Wadirin, Wadirin; Setiyo, Edi; Adanta, Dendy; Marwani, Marwani; Costa, Anthony (Universitas Sriwijaya, 2025)
This study explores the utilization of photovoltaic solar panels as a source of electrical energy to meet the needs in hard-to-reach areas. Using experimental methods, data were collected during observations from September 13 to September 18, 2024, encompassing measurements of voltage, current, and solar radiation intensity. The results indicate that the highest panel efficiency reached 25.12%, while the lowest was 19.25%, significantly influenced by sunlight intensity and panel temperature. Additionally, the highest convective heat transfer coefficient was recorded for Panel 1 at 96.64 W/m²K, showing a direct relationship with thermal conditions. This research emphasizes the importance of system design and the management of environmental factors to enhance panel efficiency. These findings open opportunities for the development of cooling technologies and more efficient energy conversion in the future.